Ultrasound Findings in Patients With Femoracetabular Impingement Without Radiographic Osteoarthritis: A Pilot Study. (11th September 2018) - Orellana, Cristóbal; Moreno, Mireia; Calvet, Joan; Navarro, Noemí; García‐Manrique, María; Gratacós, Jordi
Abstract : Objectives: To assess ultrasound (US) abnormalities in patients with clinical and radiographic features of femoracetabular impingement (FAI) without radiologic osteoarthritis. Methods: This study included patients aged 50 years or younger with hip pain and clinical and radiographic signs suggestive of FAI but without radiographic hip osteoarthritis. Demographic characteristics, the symptom duration, and the radiologic type of FAI were recorded. Ultrasound examinations assessed for anterior labral abnormalities, osteophytes, bone cortex irregularities, capsular distension, and acetabulofemoral and femoral head‐to‐neck distances. A balanced group of healthy volunteers was used as control participants. Results: Forty‐four patients with FAI were evaluated. Ultrasound changes were found in 93.2% of patients, with 63.6% showing some kind of labral abnormality, 40.9% showing articular cartilage abnormalities, 38.6% showing bone contour irregularities, and 29.5% showing osteophytes. The cartilage width and symptom duration were inferior in patients with a damaged articular surface compared with those without ( P = .005 and .012, respectively). Patients showing osteophytes on US examinations were slightly older ( P = .048). Patients with cam‐type FAI were more frequently male ( P = .0001) and younger ( P = .022) compared with those who had pincer‐type FAI and also had a shorter symptom duration ( P < .05). Patients with symptoms for 2 years or less had a shorter femoral cartilage width ( P = .027). Femoral head‐to‐neck distances were shorter in patients compared with controls ( P = .0005). Only 1 patient in the control group showed some US abnormality. Conclusions: Ultrasound showed detected abnormalities in a significant proportion of patients with symptomatic FAI in early phases of the disease. Additional longitudinal studies are warranted to establish the prognostic importance of these US changes.© 2018 by the American Institute of Ultrasound in Medicine